Simulation of Low Thrust Spacecraft Guided Motion for a Number of Missions in the Solar System. (2017) - Fain, Maxim K.; Starinova, Olga L.; Gorbunova, Irina V.; Khabibullin, Roman M.; Shornikov, Andrey Yu.; Kuptsov, Vyacheslav V.
Abstract: Models of spacecraft guided motion in the gravitational fields of different configurations were developed. Parameterization of the optimal control laws for all the trajectory segments of the spacecraft moving in the N-body gravitational field was realized. The dependence patterns of control laws on mission purposes were determined. The simulation of the number of missions in the Solar system was performed: low Earth orbit – L1 and L2 of the Earth-Moon and the Sun-Earth systems, L1 – L2 and L2 – L1 of the Earth-Moon and the Sun-Earth systems, low Earth orbit – asteroid Eros, low Earth orbit – Venus, low Earth orbit – Mars. Moreover, the Venus gravity assist maneuver was considered.